Effects of broth composition and light condition on antimicrobial susceptibility testing of ionic silver - Zhang, S.; Liu, Lihong; Pareek, Vishnu; Becker, Thomas; Liang, J.; Liu, Shaomin (Elsevier Inc, 2014)
In this study, the minimum inhibitory concentrations (MICs) of AgNO3 against bacteria were investigated in a variety of microorganism culture broths. Broth- and light-dependent MIC values were observed and correlated negatively with nano-Ag speciation development. We advocate here the importance of broth and light standardization in Ag antimicrobial test.